IMPLIKASI TEORI HUMANISTIK DAN KECERDASAN GANDA DALAM DESAIN PEMBELAJARAN PAI - Mahrus Mahrus; Zubdatul Itqon (Piwulang: Jurnal Pendidikan Agama Islam, 2020)
This study aims to describe the implications of humanistic learning theory and multiple intelligences on learning Islamic education. This research is library research. Research data were obtained from books and scientific journal notes. The results showed that Abraham Maslow's humanistic theory aims to humanize humans as early as possible as their nature. The learning process is considered effective if students understand themselves and their surroundings. Students in a series of learning should try so that sooner or later they can actualize themselves as best as possible. Meanwhile, Howard Gardner's theory of multiple intelligences is oriented towards understanding the potential abilities of various intelligences so that their potential can be optimized according to the nature of their creation.Penelitian ini bertujuan untuk mendeskripsikan implikasi teori pembelajaran humanistik dan kecerdasan majemuk terhadap pembelajaran pendidikan Agama Islam. Penelitian ini adalah penelitian kepustakaan. Data penelitian diperoleh dari buku dan catatan jurnal ilmiah. Hasil penelitian menunjukkan bahwa Teori humanistik Abraham Maslow bertujuan untuk memanusiakan manusia sedini mungkin sebagaimana fitrahnya. Proses pembelajaran dianggap efektif jika siswa memahami dirinya dan lingkungan sekitarnya. Siswa dalam suatu rangkaian pembelajaran hendaknya berusaha agar cepat atau lambat ia dapat mengaktualisasikan dirinya sebaik mungkin. Sedangkan teori kecerdasan majemuk Howard Gadrdner berorientasi pada memahami kemampuan potensi berbagai kecerdasan agar potensinya dapat optimal sesuai dengan fitrah penciptaannya.